2023
DOI: 10.3390/nu15041061
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Indices and the Nutritional Properties of Karakul Sheep Meat

Abstract: This study aimed to evaluate the fatty acid profile and health lipid indices of sheep meat (from 52 Karakul sheep from NE Romania). The effect of age at slaughter and the influence of muscle region were studied for nutritional parameters, especially the fatty acids from lipid fractions. Based on the fatty acid profiles and lipid contents, the sanogenic indices were determined for two sheep muscle groups. Thus, two different muscle regions from lamb and adult sheep were analysed from both genders, the Longissim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…FAs, as a crucial constituent of adipose tissue, contribute to flavor, nutritional value, and physiological function [29,30]. According to the results we obtained from the fatty acids analyzed in this study, C16:0, 9c-C18:1, and C18:0 were the most abundant in the SAT.…”
Section: Discussionmentioning
confidence: 51%
“…FAs, as a crucial constituent of adipose tissue, contribute to flavor, nutritional value, and physiological function [29,30]. According to the results we obtained from the fatty acids analyzed in this study, C16:0, 9c-C18:1, and C18:0 were the most abundant in the SAT.…”
Section: Discussionmentioning
confidence: 51%
“…The smaller values of AI present a greater protective potential for coronary artery diasese. however, the AI was below the recommended value meat (1.0) [ 65 ], but they were better than the average found [ 66 ], who observed an average value of 0.56.…”
Section: Discussionmentioning
confidence: 68%
“…Thus, in the specialized literature, the superior value of game meat is confirmed by a higher content of some essential amino acids. Various studies reported comparative data regarding the higher values of the total proteins of game meat and of domestic farm species [ 77 , 98 ]. Accordingly, Okuskhanova et al [ 76 ] revealed that maral meat has a higher content in essential amino acids compared to beef.…”
Section: Resultsmentioning
confidence: 99%